2006
DOI: 10.3758/bf03193395
|View full text |Cite
|
Sign up to set email alerts
|

Complex span tasks, simple span tasks, and cognitive abilities: A reanalysis of key studies

Abstract: . Within the investigation of memory span tasks, there are two basic theoretical issues presumably germane to the understanding of individual differences in cognitive abilities (Miyake, 2001). First, to what extent are individual differences in memory span tasks domain specific or domain general? Friedman and Miyake (2000) and Mackintosh and Bennett (2003) highlighted the domain-specific components of complex span tasks, whereas Turner and Engle (1989), Kane et al. (2004), andShih (2004) emphasized the domain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
144
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(168 citation statements)
references
References 35 publications
17
144
3
4
Order By: Relevance
“…In contrast to these studies, Colom, Rebollo, Abad, and Shih (2006) reported that simple span performance predicted Gf. They reanalyzed data from five previous studies using the model and analyses from .…”
Section: Similarities Between Simple and Complex Span Performancecontrasting
confidence: 39%
“…In contrast to these studies, Colom, Rebollo, Abad, and Shih (2006) reported that simple span performance predicted Gf. They reanalyzed data from five previous studies using the model and analyses from .…”
Section: Similarities Between Simple and Complex Span Performancecontrasting
confidence: 39%
“…On one hand, it has been suggested that short term memory is the best predictor of the relationship between WM and intelligence (see Colom et al, 2006). This view has found support from the consideration that simple span tasks with long lists tap the same controlled mechanism as complex span tasks (Unsworth & Engle, 2006).…”
Section: Models Of Working Memory and Short-term Memorymentioning
confidence: 52%
“…The possibility that WM and STM might reflect different functions and be differently related to intelligence is still debated (Alloway, Gathercole, & Pickering, 2006;Colom, Rebollo, Abad, & Shih, 2006). On one hand, it has been suggested that short term memory is the best predictor of the relationship between WM and intelligence (see Colom et al, 2006).…”
Section: Models Of Working Memory and Short-term Memorymentioning
confidence: 99%
“…First, memory performance is much reduced relative to comparable memory tasks without processing demand (so-called simple-span tasks). Second, combinations of memory and processing, as in complex span, are better predictors than simple span for performance on complex cognitive tasks (Ackerman, Beier, & Boyle, 2005;Daneman & Merikle, 1996; but see Colom, Rebollo, Abad, & Shih, 2006). Why does concurrent processing impair short-term storage?…”
mentioning
confidence: 99%